تكامل المواثيق الدولية في مجال إرساء مبدأ المساواة بين التشريعات الوطنية والمواثيق الدولية - الشديفات, شادي عدنان (Journal of Legal Sciences, 2020)
Together with equality before the law and equal protection of the law without any discrimination, non-discrimination provides the foundation for the enjoyment of human rights. As Shestack has observed, equality and non-discrimination “are central to the human rights movement." This paper offers an overview of the sources of nondiscrimination and the historical background of this term. Also it discusses the legal principals of the right of equality and non-discrimination through the U. N. Charter (UNCHR) and the Universal Declaration of Human Rights (UDHR) and the scope of the right to equality and nondiscrimination and State obligations.